The Pathogenesis of Oxidative Stress-Induced Chloasma and Its Therapeutic Implications - Wu Q; Zheng H; Wu J; Tang Y; Cheng H (Clinical, Cosmetic and Investigational Dermatology)
Qingqing Wu,1 Huilan Zheng,1 Jingping Wu,2 Yuruo Tang,3 Hongbin Cheng1 1Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China; 2Department of Medical Aesthetics, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China; 3Department of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Hongbin Cheng, Email chenghongbin@cdutcm.edu.cnAbstract: The majority of oral and topical skin-whitening products, as well as chemical peels, are commonly used to treat chloasma, a challenging skin pigmentation disorder. However, the therapeutic efficacy of these treatments often falls short of patients’ expectations and is accompanied by notable side effects. Oxidative stress, characterized by an imbalance between oxidation and antioxidation, plays a crucial role in various clinical conditions and leads to oxidative damage, including cellular dysfunction, DNA damage, protein and lipid peroxidation, and even irreversible cell death. Recent research has shown that the onset of chloasma is closely associated with oxidative stress. This review explores the role of oxidative stress in the pathogenesis of chloasma and examines the related signaling pathways and biomarkers. Our findings suggest that antioxidant therapy can enhance the effectiveness of chloasma treatment by inhibiting tyrosinase activity and reducing melanin production. We hope this review will provide a theoretical foundation for future antioxidant-based treatments for chloasma.Keywords: oxidative stress, chloasma, pathogenesis, antioxidant therapy, review